Isolated sphenoid polyp: a cause of headache - Galagali, J. R.; Singh, Roohie; Kumar, Santosh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Isolated sphenoid sinus polyp is a rare clinical situation. It might be an incidental finding while investigating a case of headache. We report a case of 21 years old male who presented with history of headache since 6 months. Diagnostic nasal endoscopy (DNE) revealed a right nasal mass which was confirmed by computed tomography (CT) of paranasal sinuses (PNS). The patient underwent Functional endoscopic sinus surgery (FESS).This paper emphasizes importance of correct diagnosis and consideration of sphenoid sinus disease as differential diagnosis of patients with headache.